Breast cancer in adolescents and young adults. Issue 12 (28th August 2018) - Johnson, Rebecca H.; Anders, Carey K.; Litton, Jennifer K.; Ruddy, Kathryn J.; Bleyer, Archie
Abstract: Breast cancer is the most common cancer of adolescents and young adult (AYA) women aged 15 to 39 years, accounting for 5.6% of all invasive breast cancer in women. In comparison with older women, AYAs are more likely to have familial cancer predisposition genes, larger breast tumors, unfavorable biological characteristics, distant metastatic disease at diagnosis, and adverse outcome. Endocrine therapy and some chemotherapy recommendations differ between young and older women. AYAs require coordinated multidisciplinary care, treatment regimens that minimize late effects such as premature menopause and osteoporosis, and proactive management of psychological and sexual health during and after cancer treatment.